Analysis of the tax systems of the countries that make up the Pacific Alliance - Duran – León, Isaí; Pinto – Arrieta, Carlos Alberto (Universidad Francisco de Paula Santander, 2018)
The Pacific Alliance began in April 2011 and was formalized in June 2012 by Colombia, Chile, Mexico and Peru, which seeks to create an integration zone composed of free movement of goods, services, capital and people. Its objective is to promote growth, development and competitiveness in order to improve living conditions and reduce the socioeconomic gaps that affect the population. Since its inception, the alliance has made notable progress, such as the Complementary Agreement to the Main Framework (2014) to expand trade agreements and the Latin American Integrated Market (MILA) for financial integration. However, trade liberalization faces challenges, including tax barriers affecting sectors such as film and publishing. Countries have implemented tax reforms to comply with the agreements, but low revenue collection compared to GDP poses challenges. Factors such as economic informality and the complexity of the tax system contribute to this situation. The first objective is to analyze the types of taxes that exist in the member countries of the Pacific Alliance, the second objective is to describe the characteristics of their tax systems (Chile, Colombia, Mexico and Peru) and the third objective is to examine the connection between their tax systems and the current Framework Agreement that governs them. The results obtained made it possible to distinguish which are the laws, norms and decrees that govern the tax systems under study, as well as to know and determine the nature of the taxes and who manages them in each country and finally to analyze the relationship that exists in the tax systems.